PEMBERDAYAAN KELOMPOK USAHA ISTRI NELAYAN DI BIDANG HASIL PERIKANAN MELALUI BUMDesa DESA SUNGAI LUMPUR KECAMATAN CENGAL KABUPATEN OGAN KOMERING ILIR - Meldy Triansyah (Department of Sociology, Faculty of Social and Political Sciences, Sriwijaya University, 2021)
The purpose of this study is to determine the strategy of empowering fishermen wife business groups based on local potential in Sungai Lumpur Village, Cengal District, Ogan Komering Ilir Regency and to determine the supporting and inhibiting factors in empowering fishermen wife business groups in Sungai Lumpur Village, Cengal District, Ogan Komering Ilir Regency. The result of the research is the strategy of empowering fishermen's wife business groups through BUMDesa Maju Bersama, which is to encourage and raise awareness of fishermen's wife business groups, develop the potentials of fishermen's wife business groups, provide training to fishermen's wife business groups, provide guidance to fishermen's wife business groups, provide facilities in the form of business capital and infrastructure for business needs, balancing in empowering to prevent unbalanced competition, forming cooperation with institutions and business partners and supporting positive changes in fishermen's wife business groups in the field of fishery products by providing marketing. Supporting factors in empowering fishermen wife business groups are business capital, production equipment and business partners of BUMDesa Maju with Sungai Lumpur Village such as the PMD Office, the UMKM Cooperative Office, the Industry and Trade Service and Partnership Partnerships. The inhibiting factor in empowering fishermen wife business groups is the level of education and knowledge, where education and knowledge make the community, especially fishermen wife business groups, partially not participate in the empowerment carried out by BUMDesa Maju Bersama so that BUMDesa experiences difficulties in empowering fishermen wife business groups on a group scale the big one.